2016
DOI: 10.1002/mawe.201600530
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium‐carbon nanotubes composites produced from friction stir processing and selective laser melting

Abstract: Aluminium reinforced with multi-wall carbon nanotubes was produced using friction stir processing and selective laser melting. Very fine grains were successfully achieved in both methods with high Vickers hardness values. Cavities were present in selective laser melting of AlSi10Mg reinforced with multi-wall carbon nanotubes parts resulting in higher stress concentration brittle fracture appearance. The high laser absorption and higher thermal conductivity of multi-wall carbon nanotubes resulted in the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The same reaction was detected also by Chang et al, who reported the formation of non‐elongated Al 4 SiC 4 grains . Du et al compared the mechanical properties of AlSi10Mg and AlSi10Mg‐MWCNTs produced via LPBF with the corresponding materials obtained by casting . It was pointed out that, even if the LPBF process produces a huge increase in the mechanical properties of the aluminum alloy, the introduction of the second phase in the LPBF samples reduces the AlSi10Mg mechanical properties.…”
Section: Introductionsupporting
confidence: 57%
“…The same reaction was detected also by Chang et al, who reported the formation of non‐elongated Al 4 SiC 4 grains . Du et al compared the mechanical properties of AlSi10Mg and AlSi10Mg‐MWCNTs produced via LPBF with the corresponding materials obtained by casting . It was pointed out that, even if the LPBF process produces a huge increase in the mechanical properties of the aluminum alloy, the introduction of the second phase in the LPBF samples reduces the AlSi10Mg mechanical properties.…”
Section: Introductionsupporting
confidence: 57%
“…Recently, friction stir processing has exposed the great potential for fabricating surface composites owing to its solid-state nature [8][9][10][11][12]. Friction stir processing is a unique variant of friction stir welding process, which has the same process principle of the friction stir welding [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of CNTs into the AlSi10Mg matrix can induce a transition in the solidification regime, shifting from a dendritic microstructure to a cellular-dendritic microstructure [162,163];…”
mentioning
confidence: 99%
“…Vaporization and decomposition of CNTs due to the interaction with the laser, leading to the generation of gases [82,158,162].…”
mentioning
confidence: 99%
See 1 more Smart Citation